Climate Change in Cyprus: review of the impacts and outline of an adaptation strategy - Zachariadis, Theodoros (My University, 2016)
According to the current scientific consensus, warming of the global climate system seems to be unambiguous and is most likely due to anthropogenic emissions of greenhouse gases. Anthropogenic climate change has been characterised as ‘the largest market failure’ that mankind has ever been faced with. Mediterranean Europe is expected to experience the most adverse climate change effects compared to other European regions. Cyprus, an island state in the south-east Mediterranean, already has a semi-arid climate, with hot summers and mild winters, and the most severe water scarcity problem in Europe. The island is situated on a hot spot and is projected to face significant temperature increases and decline in precipitation levels. This book addresses in a complete yet concise manner the knowledge available by the end of 2015 about expected impacts from climate change in Cyprus and outlines the main ingredients of an adaptation strategy.
Keywords: Climate adaptation; Climate impacts; Greenhouse gases; South-east Mediterranean